2020
DOI: 10.1039/c9dt04485j
|View full text |Cite
|
Sign up to set email alerts
|

A nanohybrid self-assembled from exfoliated layered vanadium oxide nanosheets and Keggin Al13 for selective catalytic oxidation of alcohols

Abstract: A porous V2O5–Al13 nanohybrid based on the self-assembly of Keggin Al13 and exfoliated V2O5 nanosheets for selective oxidation of alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…As a representative intercalant, Al 13 has been reported to hybridize with two-dimensional materials to form a nacre-like structure. Although the theoretically calculated diameter of the Al 13 polycation is 0.86 nm, the enhancement of the layer structure after pillaring is always much smaller than the theory diameter of Al 13 polycation, such as p-MnO 2 –Al 13 (2.1 Å), MnO 2 –Al 13 (3.3 Å), and V 2 O 5 –Al 13 (7.0 Å) . Limited explanation for this anomalous phenomenon was revealed in the literature, but we can infer that Al 13 in the interlayer spacing could not be simplified to occupy a rigid volume, and the final d -spacing depended on the complex interactions between Al 13 with a changeable size and bilateral nanosheets.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As a representative intercalant, Al 13 has been reported to hybridize with two-dimensional materials to form a nacre-like structure. Although the theoretically calculated diameter of the Al 13 polycation is 0.86 nm, the enhancement of the layer structure after pillaring is always much smaller than the theory diameter of Al 13 polycation, such as p-MnO 2 –Al 13 (2.1 Å), MnO 2 –Al 13 (3.3 Å), and V 2 O 5 –Al 13 (7.0 Å) . Limited explanation for this anomalous phenomenon was revealed in the literature, but we can infer that Al 13 in the interlayer spacing could not be simplified to occupy a rigid volume, and the final d -spacing depended on the complex interactions between Al 13 with a changeable size and bilateral nanosheets.…”
Section: Discussionmentioning
confidence: 68%
“…Although the theoretically calculated diameter of the Al 13 polycation is 0.86 nm, the enhancement of the layer structure after pillaring is always much smaller than the theory diameter of Al 53 and V 2 O 5 − Al 13 (7.0 Å). 54 Limited explanation for this anomalous phenomenon was revealed in the literature, but we can infer that Al 13 in the interlayer spacing could not be simplified to occupy a rigid volume, and the final d-spacing depended on the complex interactions between Al 13 with a changeable size and bilateral nanosheets. Moreover, the introduction of large Al 13 would negatively affect the Ti 3 C 2 T x membrane stability because the steric effect increases the interlayer spacing while reducing the van der Waals force between two Ti 3 C 2 T x nanosheets.…”
Section: Discussionmentioning
confidence: 77%
“…2e). The free spacing, upon partial removal of water molecules 42,43 , is narrowed from 6.6 Å (20 °C) down to 6.1 Å (60 °C) and then stabilizes even at 100 °C (inset of Fig. 2e).…”
Section: Subnanochannel Activation and Conformal Packing Of Cnsmentioning
confidence: 99%
“…It was found that V 2 O 5 has a narrow band gap (2.2 eV), requires little energy, and shows superior catalytic activity in partial oxidation. [3][4][5][6][7] The crystal structure and band structure of V 2 O 5 are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%